ELECTORAL REFORMS IN INDIA: A LOOK BACK AND A WAY FORWARD - BRIJ MOHAN DUTTA, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In recent decades, the funding of elections has grown to be a significant concern. It is generally accepted that the price of contesting elections has increased well beyond the permitted expenditure thresholds. This has led to a lack of transparency, rampant corruption, and the prevalence of so-called "black money." A variety of concerns related to election administration also require attention. Elections are difficult to hold because of the enormous size of the electorate, but this should not be used as an excuse for problems like booth capturing, voter intimidation, falsified voter registration records, widespread election rigging, other irregularities at the polls, the prevalence of ineffective candidates, and the misuse of religion and caste to influence voters. This paper provides a list of potential remedies to these issues. The proliferation of insignificant parties, the recognition and de-recognition procedures, the disclosure of political parties' assets and liabilities, and the auditing and publication of those assets and liabilities are all significant issues that are addressed in this paper with regard to the role of political parties in the electoral system. This background paper's goals are to review some of the most important problems with our electoral system and to quickly look at the proposals made in this respect by several previous committees. In order to enhance our electoral system, significant adjustments must be made, and it is intended that this background paper will serve as a springboard for a fresh national conversation on these issues.